2019
DOI: 10.3390/ani9070444
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine TMEM95 p.Cys161X Mutation in 13 Chinese Indigenous Cattle Breeds

Abstract: Chinese indigenous cattle breeds have abundant genetic resources, which are valuable for the molecular breeding of cattle around the world. Thus, identifying important candidate genes and their genetic markers is very important for cattle molecular breeding. A previous study found that a nonsense mutation (rs378652941, c.483C > A, p.Cys161X) in the bovine transmembrane protein 95 gene (TMEM95) seriously reduced the reproductive performance in bulls, but few studies have detected this mutation in Chinese ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The results showed that eight articles studied TMEM95 ( Table 1 ). The main objectives of these articles were to molecularly characterize TMEM95 [ 20 , 22 , 31 , 35 ] or to determine the cause or effect of a certain mutation, including nonsense mutations [ 23 , 24 ], synonymous mutations [ 32 ] and insertion/deletion mutations [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that eight articles studied TMEM95 ( Table 1 ). The main objectives of these articles were to molecularly characterize TMEM95 [ 20 , 22 , 31 , 35 ] or to determine the cause or effect of a certain mutation, including nonsense mutations [ 23 , 24 ], synonymous mutations [ 32 ] and insertion/deletion mutations [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a nonsense mutation (rs378652941, c.483C>A, p.Cys161X) in the bovine transmembrane protein in the VI exon part of the TMEM95 gene seriously reduced the reproductive capacity of bulls. Since the c.483C>A mutation can serve as a potential genetic marker for the selection of bulls with higher fertility, in the present study, T‐ARMS‐PCRs and PCR‐RFLP analysis methods were used to identify genetic variants at the TMEM95 gene locus, DNA sequencing method; however, the authors did not reveal mutations c.483C>A in the studied animals carriers (Zhang et al., 2019).…”
Section: Literature Reviewmentioning
confidence: 87%
“…Sperm IZUMO1 (1) and egg JUNO (2) mediate the only known cell surface interaction between mammalian gametes. Recent reports suggested that Tmem95 (encoding transmembrane protein 95) mutant cattle exhibit impaired male fertility (3, 4); Tmem95 knockout mice show male-specific sterility, producing sperm that can bind to, but do not fuse with eggs (5, 6). Tmem95 encodes a sperm acrosomal membrane protein, which re-localizes to the equatorial segment of the sperm head (3, 6) where membrane fusion with the egg takes place (7, 8).…”
Section: Introductionmentioning
confidence: 99%